Insurance and inequality in sub-Saharan Africa: Policy thresholds - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2020)
In this study, we examine how insurance affects income inequality in sub-Saharan Africa, using data from 42 countries during the period 2004-2014. Three inequality variables are used, namely: the Gini coefficient, the Atkinson index and the Palma ratio. Two insurance premiums are employed, namely: life insurance and non-life insurance. The empirical evidence is based on the Generalized Method of Moments (GMM). Life insurance increases the Gini coefficient and increasing life insurance has a net positive effect on the Gini coefficient and the Atkinson index. Non-life insurance reduces the Gini coefficient and increasing non-life insurance has a net positive effect on the Palma ratio. The analysis is extended to establish policy thresholds at which increasing insurance premiums completely dampen the net positive effects. From the extended analysis, 7.500 of life insurance premiums (% of GDP) is the critical mass required for life insurance to negatively affect inequality, while 0.855 of non-life insurance premiums (% of GDP) is the threshold required for non-life insurance to negatively affect inequality. Policy thresholds are provided at which insurance penetration decreases income inequality in sub-Saharan Africa.
Keywords: I28; I30; I32; O40; O55; 330; Insurance; Inclusive development; Africa; Sustainable Development